Pemberdayaan Petani Budidaya Sayur di Lahan Gambut Dangkal dengan Aplikasi Teknologi Pengelolaan Air dan Penguatan Kapasitas Kelembagaan - Nilna Amal; Mira Yulianti; Eddy Nashrullah; Eko Zulkifli (Universitas Lambung Mangkurat, 2026)
Caraka Jaya Village, Liang Anggang District, has significant agricultural potential, particularly for vegetables. Farmers in the village grow various types of vegetables on peatlands and produce quite good yields. However, over the past two years, there has been a phenomenon where yields have decreased. This is suspected to be due to excessive exposure to chemical fertilizers and pesticides. Furthermore, some farmers complain about limited water resources, forcing them to only plant according to the availability of rainwater. Therefore, they desire a more secure water source, so they have proposed building groundwater wells with a simple irrigation network, a simple technology application in peatlands. Furthermore, the application of organic fertilizer, as a continuation of previous community service activities, is also being carried out to prevent the proliferation of pests and to increase agricultural production. Another necessary activity is providing communication strategy training to strengthen institutional capacity so that farmers are empowered to negotiate with collectors not only as individuals but also as institutions representing the interests of farmers. The results of this empowerment are expected to improve the lives of farmer groups that are part of the farming community, thereby boosting the economy and supporting the realization of environmentally friendly agriculture.